Generative Artificial Intelligence and National Sovereignty: Indonesia's Position in a Fragmented Digital Economy - Dirgantara, Tarsa (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Generative artificial intelligence (Generative AI) is one of the most disruptive technologies in the global digital economy. Its presence not only brings opportunities for innovation, but also poses geopolitical challenges, especially in the context of the fragmentation of the global digital economy known as the splinternet. Indonesia, with the largest digital economy potential in Southeast Asia, risks becoming a passive consumer of foreign technology that can weaken national sovereignty. This study aims to analyze the implications of global digital economy fragmentation on Indonesia's national sovereignty, evaluate the role of generative AI in supporting or weakening this sovereignty, and formulate policy strategies that can strengthen Indonesia's position in international digital economy governance. The research uses a descriptive qualitative approach with normative-empirical analysis. Data was obtained through literature studies, analysis of policy documents, and in-depth interviews with regulators, industry players, and academics. The data analysis technique was carried out by thematic analysis and content analysis of international documents and national regulations related to AI. The results of the study show that global digital fragmentation puts Indonesia in a vulnerable position as a technology adopter, with the risk of dependence on foreign platforms. This dependence has an impact on weakening data sovereignty, reduced regulatory independence, and increasing national security vulnerabilities. However, there are opportunities through three main strategies: strengthening national regulations, developing local innovations based on Indonesian data, and digital diplomacy in international forums.